Photo-gated and self-powered three-dimensional DNA motors with boosted biostability for exceptionally precise and efficient tracing of intracellular survivin mRNA - Liu, Yu-Heng; Gao, Jia-Ling; Liu, Jun-Xian; Liu, Da; Fang, Wen-Kai; Zheng, Bei; Tang, Hong-Wu; Li, Cheng-Yu (Biosensors & bioelectronics, 2021)
Benefiting from the outstanding signal amplification effect and the admirable construction flexibility, the currently proposed DNA motors (particularly DNA walkers) based biosensing concepts have provided a forceful fluorescence imaging tool for intracellular detection. Even so, this promising sensing means is not only subject to poor controllability and prone to produce false signals but also requires exogenous powering forces owing to the common employment of DNAzyme. In response to these challenges, we are herein motivated to present some meaningful solving strategies. For one thing, the surfaces of gold nanoparticles are conducted with a photo-gated walking behavior by introducing a photocleave mode, under which the light-switchable DNA walkers are capable of being selectively activated via an external ultraviolet source to faultlessly prevent the sensing frame from being pre-initiated during cellular uptake and intracellular delivery. For another, the intracellular biothiols are consumed by MnO2 nanosheets to effectively avoid the competitions to Au–S bonds to eliminate potential false outputs and also self-supply sufficient cofactors (Mn2+) to actualize a self-powered operation pattern as well as facilitate the endocytosis process. Following these breakthroughs, a favorable analysis performance towards a model tumor biomarker (survivin mRNA) is endowed with the newly raised biosensor, whose sensitivity is low to pM level with a sound specificity for identifying single base mismatching. Moreover, the significantly improved autonomous three-dimensional DNA walkers can be used to determine and dynamically trace the targets in live cancer cells with an exceptional precise and efficient manner, commendably impelling the sensing ability of DNA motors in biological specimens. [Display omitted] •A photo-gated DNA walker is constructed and this motor system can be selectively activated via an external light source .•MnO2 nanosheets are employed to consume intracellular biothiols and also actualize a self-powered operation pattern.•The innovative photo-gated and self-powered fluorescent biosensor presents a good assay ability towards survivin mRNA.•The high-performance biosensor can serve as an exceptional precise and efficient imaging tracer in live cancer cells.